PROSES DAN PENGAWASAN PEMUATAN CARGO DOMESTIK LCL MELALUI LAUT PADA PT KITRANS JAKARTA - Samiyono; Kwartama, Agung (Sekolah Tinggi Ilmu Ekonomi GICI, 2024)
The domestic LCL (Less than Container Load) cargo loading process via sea freight plays a crucial role in logistics and goods transportation in Indonesia. PT Kitrans Jakarta, as a company specializing in this sector, faces various challenges in monitoring and managing cargo loading. This journal provides an in-depth discussion of the loading process, monitoring mechanisms, and factors influencing the efficiency and effectiveness of LCL shipments. Data reveals that Indonesia's LCL shipping market is experiencing significant growth, with an estimated annual volume increase of 10% (Indonesian Logistics Association, 2022). Through case studies and statistical analyses, this journal identifies best practices in cargo loading supervision and offers recommendations to enhance the operational performance of PT Kitrans. The findings of this study are expected to serve as a reference for other logistics companies in optimizing the LCL cargo loading and monitoring process in Indonesia